Active Older Adults at Home: Developing an Online Physical Program in the Covid-19 Pandemic - Mattana Griebler , Eliane (2022)
The objective is to describe and analyze an online physical program for the older adults in the Covid-19 pandemic, regarding motivation and perception of results. Adherence to multicomponent physical training (3 weekly sessions, 10 months) was 57% and with more than 60% adherence. The perceived results were related to physical aspects, functionality, social interaction and time occupation. Online physical exercise was feasible for the older adults, but further studies are needed.